Characteristics of joint kinetics of the lower limb during take-off motion in high jump - Tobe, N.; Kariyama, Y.; Hayashi, R.; Kigoshi, K.; Ogata, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
In the take-off motion of the high jump, huge power exerted by the lower limb is required in a very short time. Consequently, to achieve the take-off motion, improvement of power exertion ability is important, and most high jumpers work to achieve this. However, the components of the kinetics that contribute to high jump performance are unknown. This study investigated lower limb joint kinetics during the take-off phase of the high jump and the relationships between kinetic variables and performance. Seven male high jumpers were investigated. Their take-off motions were filmed using an infrared camera (Vicon Motion System, 250 Hz), and the ground reaction force was recorded using a force platform (Kistler, 9287C, 1000Hz). The coefficients of correlation between the vertical velocity of the center of gravity of the whole body (CG) at the moment of take-off and kinetic variables were calculated. The following results were obtained: 1. The muscles involved in hip extension play a primary role in shock absorption at the moment of touchdown. Furthermore, the muscles involved in hip abduction, knee extension and ankle plantarflexion play a significant role in lifting the body in addition to the above functions. 2. The concentric power produced by hip abductors during the take-off motion may increase vertical velocity of the CG at the moment of take-off. 3. As it has been reported that single leg exercises impact the function of hip abductors, such exercises may improve take-off motion in the high jump. These results illustrate the characteristics of take-off motion in the high jump, and these may be studied further to plan effective training aimed at improving performance.